Reducing Unplanned Extubations in a Pediatric Intensive Care Unit: A Systematic Approach. (30th December 2009) - Rachman, Bonnie R.; Watson, Robin; Woods, Norline; Mink, Richard B.
Abstract : Objective . To prospectively determine the rate of unplanned extubations and contributing factors and determine whether a targeted intervention program would be successful in decreasing the rate of unplanned extubations. Design . Prospective, observational study. Setting . A 10-bed Pediatric Intensive Care Unit (PICU). Patients . All intubated pediatric patients during two time periods: September 1, 2000–March 31, 2001 and November 1, 2001–April 30, 2002. Interventions . After determining the rate and causes of unplanned extubation, a program was developed consisting of education and a formalized endotracheal tube taping policy. Data were then collected after implementation of the program. Measurements and Main Results . Prior to the implementation of the program, there were 10 (14.7%) unplanned extubations for a rate of 6.4 unplanned extubations per 100 ventilated days. Of the ten unplanned extubations, reintubation was required in 2 (20%). Inadequate sedation, poor taping, and improper position of the endotracheal tube were the items most frequently cited as causing an unplanned extubation. Following the program, there were two (3.4%) unplanned extubations for 1.0 unplanned extubations per 100 ventilated days. Neither patient required reintubation. There were no significant differences (P > .0 5 ) in age, weight, endotracheal tube size, or duration of intubation in the two time periods. However, there was a significant decrease in both the number (P = .03 ) and the rate (P = .04 ) of unplanned extubations after the implementation of the quality improvement program. Conclusions . The rate of unplanned extubation in a PICU can be decreased with a quality improvement program that targets the institution's specific needs.